Optimizing Asset Recovery Through the Implementation of Article 12 B (Gratification) and Money Laundering in Handling Corruption Crimes - Asep Guntur R; Azis Budianto (Greenation International Journal of Law and Social Sciences, 2025)
One of the goals of the Corruption Eradication Law is asset recovery. This is evident in the Law Number 20 of 2001 modification to Law Number 31 of 1999 for the Eradication of Corruption. This is inextricably linked to lawmakers' understanding that corruption is a serious crime that harms the country's economy by causing state assets to be unlawfully transferred to corrupt officials and their associates. This research aims to analyze how law enforcement officials, specifically the Corruption Eradication Commission (KPK), can implement existing articles and laws to maximize the recovery of state financial losses due to corruption before the asset confiscation law is enacted by the government. This research uses an empirical legal research method, examining how the law works to achieve its objectives. The theory used is Nonet and Selznic's responsive legal theory. This theory teaches that law is not merely a system of regulations but examines the impact of the application of legal norms on the objectives of the law itself. According to the study's findings, law enforcement officials at the Corruption Eradication Commission (KPK) can use information from the State Officials' Wealth Report (LHKPN) to spot increases in the wealth of suspected corruption offenders in order to achieve one of the goals of the corruption law, which is the recovery of state financial losses or asset recovery, prior to the implementation of the asset confiscation law. This data is combined with secondary data from field surveys on the wealth ownership of suspected corruption perpetrators and data from other stakeholders such as the Financial Transaction Reports (PPATK), Banking, Taxation, National Land Agency (BPN), and others. This spike in wealth is then analyzed in relation to the period of the spike and correlated with the position of the suspected corruption perpetrator at the same time. Furthermore, Article 3 of Law Number 8 of 2010 concerning the Crime of Money Laundering, as well as Article 12B (Gratification) of Law Number 31 of 1999, as amended and supplemented by Law Number 20 of 2001, apply.